Implikasi Perkawinan di Bawah Tangan Terhadap Harta Anak Dan Istri (Studi Kasus di Desa Teluk Piai-Kualuh Hilir-Labura) - Irwansyah Putra; Abu Bakar; Habibullah Habibullah (Jurnal Ekshis, 2026)
Unregistered marriage is a marital practice conducted without official registration and without the presence of an authorized state official, resulting in the absence of legal protection for the parties involved. This condition often causes significant disadvantages, particularly for wives and children, in terms of legal status and property rights. Although it contradicts existing laws and regulations, unregistered marriage remains widely practiced within Indonesian society. This study aims to: (a) analyze the implications of unregistered marriage for the legal status of wives, children, and marital property (a case study in Teluk Piai Village, Kualuh Hilir District, North Labuhan Batu Regency); (b) examine the legal consequences of unregistered marriage based on Law No. 1 of 1974 on Marriage and its amendments; and (c) identify the legal remedies available to protect the rights and status of the parties concerned. This research employs a qualitative approach with a case study design through direct field observation. The findings indicate that unregistered marriage, commonly performed for religious or customary reasons, lacks explicit regulation in Indonesian legislation, resulting in considerable legal vulnerability for wives and children.